Infant Dextromethorphan and Dextrorphan Exposure via Breast Milk From Mothers Who Are CYP2D6 Extensive Metabolizers. (8th January 2022) - Shum, Sara; Yadav, Aprajita; Fay, Emily; Moreni, Sue; Mao, Jennie; Czuba, Lindsay; Wang, Celine; Isoherranen, Nina; Hebert, Mary F.
Abstract: The risk of infant exposure to dextromethorphan (DM) and its active metabolite, dextrorphan (DX), through breast milk has not been evaluated. In this study, bound and unbound DM and DX concentrations in breast milk and plasma at 2 hours post‐dose were measured in 20 lactating women (n = 20) following a single 30 mg oral dose of DM. The DM and DX concentrations in breast milk were positively correlated with their respective plasma concentrations. The breast milk‐to‐plasma (M/P) ratios of 1.0 and 1.6 and the unbound M/P ratios of 1.1 and 2.0 for DM and DX, respectively, suggested that DM and DX are extensively distributed into breast milk. The infant exposure following a single dose of 30 mg DM was estimated using breast milk concentrations of 0.33 ± 0.32 and 1.8 ± 1.0 μg/kg/day for DM and DX, respectively. The steady‐state infant exposure was estimated using the M/P ratios and previously reported area under the concentration‐time curve (AUC) of DM and DX following repeated dosing of DM 60 mg orally, twice daily, to be 0.64 ± 0.22 and 1.23 ± 0.38 μg/kg/day, respectively. Based on these estimated infant doses, the relative infant doses (RIDs) were estimated to be <1%, suggesting the infant is only exposed to a minor fraction of adult dose through breast milk; however, one nursing infant developed an erythematous rash during this study, which warrants additional research to fully elucidate the risks of infant exposure to DM and DX through breast milk.